Effect Of Aloevera Extract As Edible Coating On The Quality Of Tomato Fruit (Solanum Lycopersicum) Cultivars Virza F1 - Ainun Isa, Raqiqah; Indzriyani, Fiqih; Eviyati, R. Eviyati (Jurnal Agrosci, 2024)
The decrease in nutritional value and shelf life of tomato fruit after harvest is due to the fact that tomato fruit still carries out metabolic processes such as respiration and transpiration. One of the efforts to maintain the nutritional value and shelf life of tomato fruit includes edible coating using Aloevera extract. Research on aloevera extract was conducted at the Faculty of Agriculture Laboratory, UGJ Cirebon in July 2024. The research method used is the experimental method, with a complete randomized design (CRD), six treatments of aloevera extract concentration and repeated four times. Variables measured included weight loss, total soluble solids content, vitamin C, moisture content and shelf life. Tests were conducted using analysis of variance and DMRT test.The results showed that differentconcentrations of aloevera extract gave differences to weight loss, total soluble solids content, vitamin C content, water content and shelf life of tomato fruit. Tomatoes that are notcoated with aloevera extract produce the highest weight loss and vitamin C content. The longest average shelf life of tomato fruit was obtained in the treatment of aloevera extract concentrations of 80% and 100% with an average shelf life of 17.50 and 18.25 days, respectively.